WGMs on-Chip Design for Interdisciplinary Studies - Preecha P. Yupapin (My University, 2013)
Light in a PANDA ring resonator system for coated and uncoated materials have been proposed and discussed. The input waves (lights) can be in the forms of soliton, Gaussian pulses, photon or matter wave. The trapped electron motion around the PANDA ring can also be generated, in which the matter wave concept is formed within the PANDA ring waveguide. From the results, we found that the whispering gallery mode (WGM) can be generated due to coupling effects of the two nonlinear side rings, which have shown many interesting results and aspects. We found that four behaviors of light, for instance, fast, slow, stopping and storing can be manipulated and seen simultaneously by PANDA ring planar waveguide, which can be fabricated and tested on-chip, which is also suitable to implement in the laboratory.
Keywords: Waveguide; Mechanical and Optical Resonators